2005
DOI: 10.1029/2004jd005459
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical ammonia emission parameterization for use in air pollution models

Abstract: [1] A parameterization of the temporal variation of ammonia (NH 3 ) emission into the atmosphere is proposed. The parameterization relies on several simple submodels reflecting emission from stores and barns, agricultural practice in application of manure, and emission from grown crops. Some of the submodels depend on a simple crop growth model, which again depends on temperature variations throughout the year. The parameterization reflects the differences in agricultural practices, differences in the climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
160
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(187 citation statements)
references
References 46 publications
1
160
0
2
Order By: Relevance
“…Reconciling the discrepancy then requires us to better understand the bottom-up emissions from the underlying processes. Previous studies have shown that NH 3 emissions are highly sensitive to the magnitude and timing of fertilizer application as well as variations of meteorology (Søgaard et al, 2002;Gyldenkaerne et al, 2005;Paulot et al, 2014), but these factors are neither sufficiently represented nor well evaluated in the Chinese NH 3 emission estimates. Here we construct an improved bottom-up Chinese NH 3 emission inventory from fertilizer application and livestock waste, with the objective to better estimate fertilizer application practices and emission factors.…”
Section: Improving Bottom-up Estimates Of Agricultural Nh 3 Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reconciling the discrepancy then requires us to better understand the bottom-up emissions from the underlying processes. Previous studies have shown that NH 3 emissions are highly sensitive to the magnitude and timing of fertilizer application as well as variations of meteorology (Søgaard et al, 2002;Gyldenkaerne et al, 2005;Paulot et al, 2014), but these factors are neither sufficiently represented nor well evaluated in the Chinese NH 3 emission estimates. Here we construct an improved bottom-up Chinese NH 3 emission inventory from fertilizer application and livestock waste, with the objective to better estimate fertilizer application practices and emission factors.…”
Section: Improving Bottom-up Estimates Of Agricultural Nh 3 Emissionsmentioning
confidence: 99%
“…where T i and W i are 2 m (meter) air temperature in • C and 10 m wind speed in m s −1 for month i, respectively (Søgaard et al, 2002;Gyldenkaerne et al, 2005). We use the gridded (0.5 • × 0.5 • ) soil pH data from the University of Wisconsin Nelson Institute Center for Sustainability and the Global Environment (SAGE, 2015), and the soil CEC data (0.5 • × 0.5 • ) from the ISRIC-World Soil Information (ISRIC WSI, 2015) of the World Data Center for Soils.…”
Section: Emission Factor From Fertilizer Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here the main sources are livestock, manure management and application of fertilizer (Reis et al, 2009;Skjøth et al, 2011). Nearly all ammonia emissions are due to volatilization of ammonia from wet surfaces (Elzing and Monteny, 1997;Gyldenkaerne et al, 2005). Volatilization of ammonia is a physical process that is highly temperature dependent (Gyldenkaerne et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although the Eulerian approach is powerful and widely used for elucidating the chemical and physical mechanism in the atmosphere, the Lagrangian approach demonstrates key advantages in presenting sub-grid scale process, minimizing numerical diffusion, artificial dilution and computing resources. The Lagrangian approach has been widely adopted in various models in atmospheric ammonia modeling such as the FRAME model (Singles et al, 1998;Kryza et al, 2011;Zhang et al, 2011), the TREND model (Asman and van Jaarsveld, 1992;Asman, 2001), the ACDEP model (Hertel et al, 1995Gyldenkoerne et al, 2005;de Leeuw et al, 2003;Skjøth et al, 2002Skjøth et al, , 2004Skjøth et al, , 2011, The TERN model (ApSimon et al, 1994), and the NAME model (Redington and Derwent, 2002). Most existing Lagrangian models for atmospheric ammonia modeling are either box-based models or use a simplified dry chemical scheme.…”
Section: Wen Et Al: Modeling Atmospheric Ammonia and Ammoniummentioning
confidence: 99%